2020
DOI: 10.26552/com.c.2020.4.20-27
|View full text |Cite
|
Sign up to set email alerts
|

Process Efficiency Analysis of Selected Automotive Companies in Europe

Abstract: The automotive industry has lately been undergoing major changes having a considerable impact on the whole vehicle sector. This does not only refer to what is technologically new on vehicles themselves, but also to the new modern management methods, frequently associated with the Industry 4.0 concept. As well as other companies, car factories are pushing their costs downwards to increase their production efficiency. This paper analyses the economic situation of 5 car manufacturers, two of which having their fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Conforme apresentado no Quadro1 a técnica DEA é utilizada para mensurar a eficiência em diferentes setores/empresas como fabricantes de veículos (Piran et al, 2017;Papouskova et al,2020;Piran et al, 2020), microempresas chinesas (Zang et al, 2018), setor agrícola (Bobitan et al, 2023), etc. No entanto pesquisas focadas em montadoras de veículos são escassas, fato este que amplia a necessidade de mais estudos sobre o tema.…”
Section: Bobitan Et Al (2023)unclassified
“…Conforme apresentado no Quadro1 a técnica DEA é utilizada para mensurar a eficiência em diferentes setores/empresas como fabricantes de veículos (Piran et al, 2017;Papouskova et al,2020;Piran et al, 2020), microempresas chinesas (Zang et al, 2018), setor agrícola (Bobitan et al, 2023), etc. No entanto pesquisas focadas em montadoras de veículos são escassas, fato este que amplia a necessidade de mais estudos sobre o tema.…”
Section: Bobitan Et Al (2023)unclassified
“…Their results point to higher efficiency of European producers compared to Asian and American competitors. From local research there can be mentioned Papoušková et al [4], who deal with the issue of automotive industry efficiency in the Czech Republic. An overview of individual studies on a given topic is shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of studying the marketing activities of enterprises in the car market and the prospects for their effective operation, it is necessary to take into account the globalization processes [1][2], restrictions on access to natural resources and increase of their value [3][4], digitalization of society [5][6], intensification of competition [7][8] and government regulation [9][10][11], which are key factors influencing development of the automotive industry in the world. Besides that, since 2020 the world economy has largely been affected by the COVID-19 crisis [12] that has a great impact on the consumer's behavior worldwide; in general and on the global car market, in particular.…”
Section: Introductionmentioning
confidence: 99%